1980
DOI: 10.1111/j.1365-2923.1980.tb02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated patients and the assessment of medical students' interpersonal skills

Abstract: While the use of simulated patients for the assessement of medical students' skills is increasing there is little data on whether students perform differently vs real patients. The present study examined this issue using second-year medical students' ability to empathize with simulated and genuine patients. Forty second-year students each conducted two interviews which were audio-recorded and later rated by raters who had achieved a high degree of reliability using the 9-point accurate empathy scale (Truax, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 17 publications
2
62
0
2
Order By: Relevance
“…Studies investigating the usefulness of simulations for instance, have showed that students might react similarly to real and simulated patients (Sanson-Fisher & Poole 1980). In the study by Edelstein et al (2000), students thought that computer-based case simulations were better tests of clinical decision making than written shelf examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the usefulness of simulations for instance, have showed that students might react similarly to real and simulated patients (Sanson-Fisher & Poole 1980). In the study by Edelstein et al (2000), students thought that computer-based case simulations were better tests of clinical decision making than written shelf examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors use the term simulated patients (Sanson-Fisher & Poole, 1980;Norman et al, 1982), but others use the term standardised patients (Rubin & Philp, 1998). Although having quite different meanings, these two terms are often used interchangeably.…”
Section: Who Are Simulated Patients?mentioning
confidence: 99%
“…However, Sanson-Fisher & Poole (1980), when comparing medical students' performance with that of real and simulated patients, used volunteer simulators who were not 'members of the acting profession'. In a description of new medical student teaching at Michigan State University, Jason et al (1971) write that their simulated patients were 'primarily drama students from our campus' and additionally 'several housewives, some of whom had no previous acting experience'.…”
Section: Who Are Simulated Patients?mentioning
confidence: 99%
“…The results of this study may not be necessarily generalized to medical interviews between actual physicians and patients, because this study examined medical interviews strictly between students and standardized patients. However, several studies have found no significant differences in the interactions of students with simulated versus actual patients (Helfer et al 1975;Sanson-Fisher and Poole 1980). It might be possible that students who did not use the open-ended question could not perform some of the other medical interview skills to obtain medical information from patients.…”
Section: Discussionmentioning
confidence: 99%